Student Attitudes Toward Campus Diversity at the U.S. Naval Academy: Evidence From Conjoint Survey Experiments - Polga-Hecimovich, John; Carey, John M.; Horiuchi, Yusaku (Armed forces and society, 2021)
Although the value of diversity—in terms of race, ethnicity, gender, and socioeconomic status—to the U.S. military has been subject to debate, preferences for diversity at educational institutions for the military officers are rarely examined systematically. To address this, we investigate whether midshipmen at the U.S. Naval Academy favor prioritizing diversity in student admissions and faculty recruitment using conjoint analysis, a method suited for estimating attitudes on sensitive and politicized issues. The results show strong preferences in favor of applicants from disadvantaged socioeconomic backgrounds and moderate but still positive preferences for members of traditionally underrepresented racial/ethnic groups in both admissions and faculty recruitment. Midshipmen’s preferences with respect to gender are, however, less straightforward. In particular, we find a strong negative preference against gender nonbinary applicants and candidates. Our findings suggest that midshipmen’s attitudes reflect both resolved and unresolved debates that resonate throughout the armed forces.